EFEKTIVITAS PENGELOLAAN DANA DESA DALAM PEMBERDAYAAN MASYARAKAT DI DESA KONTUNAGA KECAMATAN KONTUNAGA KABUPATEN MUNA - Saputra, Salim; Nalefo, La; Jayadisastra, Yoenita (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The purpose of this study is to determine the effectiveness of village funds management in community empowerment in Kontunaga Village, Kontunaga District, Muna District in 2022. This study was using a sample of 34 people from the community who were members of the community empowerment program in Kontunaga village in 2022. The data analysis for this study was based on the proposed effectiveness formula. The results of this study show that village financial management for community empowerment in Kontunaga village consists of village financial planning, which is rated as highly effective with an effectiveness level of 95,88%. The utilization of village resources is classified as effective with an effectiveness level of 84,71%. The accountability of the village fund belongs to the effective category, and its effectiveness level is 86,67%. This shows that village resource management for community empowerment in Kontunaga Village, Kontunaga District, Muna District is truly practiced and enjoyed by the community.